The Determinants of Islamic Banks’ Stock Prices: Evidence from the GCC Countries - Muhammad Muhajir Aminy; Ahmad Sauqi (Jurnal Ilmiah Ekonomi Islam, 2020)
Islamic banks’ stock is a new interesting material to be discussed among Islamic economics scholars. The majority of Islamic banks’ stocks presents in the middle-east countries, especially those which are joining as the Gulf Cooperation Council (GCC) countries. Samples in this study were 10 Islamic banks in the Gulf Cooperation Council (GCC) countries with secondary data from their financial report. A panel data regression analysis was employed to seek the influence of all observed variables (ROA, ROE, and ICSR (zakat)) as the determinant factors toward Islamic banks’ stock prices. The study found that all the independent variables simultaneously have an impact on Islamic banks’ stock prices in that area. The study also found that the variable of ROA has a negative significant impact, the variable of ROE has a positive significant impact, and ICSR (zakat) has an insignificant impact on Islamic banks’ stock prices in the GCC countries. This study suggested all Islamic banks globally to consider investors’ sentiment on Islamic banks’ financial condition before entering the Islamic capital market